Efficacy of Antimicrobial Photodynamic Therapy for Treating Moderate to Deep Periodontal Pockets in Individuals with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis - Rodrigues, João Victor Soares [UNESP]; Deroide, Mariella Boaretti [UNESP]; Takeshita, Wilton Mitsunari [UNESP]; Garcia, Valdir Gouveia; de Molon, Rafael Scaf [UNESP]; Theodoro, Leticia Helena [UNESP] (MDPI, 2025)
Background/Objectives: Diabetes mellitus and periodontitis share a significant, bidirectional relationship. Diabetes raises the risk of periodontitis and influences its severity, impacting tissue repair and bone metabolism. Conversely, periodontal inflammation can disrupt glycemic control, further complicating this interlinked relationship. This systematic review aimed to evaluate the efficacy of antimicrobial photodynamic therapy (aPDT) as an adjunct to subgingival instrumentation (SI) in the treatment of periodontal pockets with a probing pocket depth (PPD) ≥ 5 mm in individuals with type 2 diabetes mellitus (DM2) and periodontitis. Methods: Using the PICOS framework, this review addressed the following question: “How does aPDT as an adjunct to SI compare to SI alone in treating periodontal pockets with PPD ≥ 5 mm in individuals with DM2 and periodontitis?” Databases searched included PubMed, Scopus, and Web of Science up to December 2024. Randomized clinical trials evaluating periodontal status and HbA1c levels in patients with DM2 undergoing periodontal therapy and experiencing SI were included. Patients who received adjunctive aPDT were compared to a control group that received SI alone. A meta-analysis was conducted illustrating treatment effects across groups. Results: After screening 117 studies based on titles and abstracts, three and four studies met the eligibility criteria for quantitative and qualitative analyses, respectively. The principal periodontal parameters assessed included PPD, clinical attachment level (CAL), plaque index (PI), and bleeding on probing (BOP). Forest plots for PD, BOP, PI, and CAL at baseline, three months, and six months revealed no statistically significant differences between the SI+aPDT group and the SI-only group. Glycated hemoglobin across treatment groups was not different. Conclusions: The combination of aPDT with SI provides limited clinical benefits in treating periodontal pockets with a PPD ≥ 5 mm in diabetic patients with periodontitis.
Keywords: diabetes mellitus; periodontal disease; periodontal pocket; photochemotherapy; photosensitizing agents